Prenatal care and comprehensiveness: scoping review (Research, Society and Development, 2021)
Objective: to map and discuss the state of the art of comprehensiveness in prenatal care in primary care. Methodology: review of scope guided by the research protocol of the Joanna Briggs Institute. Publications in national and international digital databases/libraries, dated between 1980-2019 were consulted. The studies were selected and analyzed according to the proposal of comprehensive care proposed by Ayres, namely the axis of needs, axis of articulations, axis of interactions and axis of purposes. Results: 26 studies were included and analyzed; the most published in the 2000s, with 17 national and 9 international studies. The achievement of comprehensiveness in prenatal care was almost exclusively linked to the axis of needs. The articulation axis and the other show difficulties in reaching interdisciplinary knowledge and practices, pointing to the need for changes in professional attitude, articulation of health care networks, cooperation between health and social sectors, participation and social mobilization. Conclusion: the state of the art revealed that prenatal care, especially built by relationships that move little towards achieving comprehensiveness, ends up hindering the construction of this principle in everyday practices.